Arts, mathematics and sciences students' attitudes toward online learning during the pandemic / Mohammad Mubarrak Mohd Yusof ... [et al.] - Mohd Yusof, Mohammad Mubarrak; Halimy, Muhamad Danial Zaha; Zulkipli, Zulinda Ayu; Luaran, Johan @ Eddy; Jain, Jasmine (UiTM Press, 2022)
The unusual coronavirus (COVID-19) outbreak in Malaysia has necessitated considerable modifications in how children are educated. As well as avoiding their friends and family, students had to become used to studying online. Remote learning has become the norm to prevent the spread of the highly contagious disease. The sudden outbreak has forced educators to transition to online modalities of instruction, notably at the university level. On the other hand, some pupils are open to online learning. But other people are apprehensive about switching from traditional to online study. Education professionals may be able to help make virtual education more engaging and efficient. The goal of this study was to see if Arts, Sciences and Mathematics students from the The Faculty of Education at Universiti Teknologi MARA (UiTM), Puncak Alam, Selangor, had different attitudes about online learning during the COVID-19 outbreak. The questionnaire was administered using Google Form to 201 students in semesters 1 to 8. The data were examined both descriptively and inferentially using SPSS. Inferential analytics include analysis of variance (ANOVA) and mean and standard deviation. Students' perceptions about effectiveness towards online learning platforms were found to be positive.